Low Dimensional Carbon Based Materials For Low Pressure Measurement Application - Haniff, Muhammad Aniq Shazni Mohammad (2015)
Advances in materials science and engineering design have enabled the realization of flexible and highly sensitive pressure sensors. To date, numerous progresses on the invention of the piezoresistive pressure sensors based on the functional nanomaterials and the diaphragm structure have been widely demonstrated, in which great attention has been centered on improvement of sensitivity by the utilization of the functional nanomaterials and the optimization of the device geometries. However, real-time detection in low pressure range (<10 kPa) with excellent sensitivity has been rarely reported by the current progress of piezoresistive pressure sensors due to two apparent reasons: (i) lack of exploitation of functional nanomaterials through a controllable synthesis method and (ii) implementation of conventional diaphragm design structure. In view of that, this dissertation is intended to develop the flexible piezoresistive pressure sensor, which mainly focuses on the sensitivity enhancement with the incorporation of newly developed low dimensional carbon based materials and diaphragm structure with IDE array to satisfy the requirement of low pressure application. The novel features of low dimensional carbon based materials for 0-D carboncapped nanoparticles, 1-D carbon nanotubes and 2-D graphene ultra-thin films have been introduced through chemical vapor deposition (CVD) and their morphology and electrical properties have been carefully characterized. Prior to the device fabrication, analyses on the characteristics of the reinforced diaphragm structure with interdigitated electrode (IDE) array have been accomplished through the CoventorWare® utilizing the finite element analysis (FEA). Parametric studies have been performed for all the simulations to evaluate the influence of geometrical parameters on the associated characteristics of interest. Two critical steps involved in the development of pressure sensor such as integration of IDE array on flexible substrate and transfer-printing method of low dimensional carbon based materials have also been demonstrated. From the characterization results of low dimensional carbon based materials, uniformity and tunable morphology of the synthesized materials at different 0-D, 1-D and 2-D configuration in a control manner was achieved with excellent electrical properties. The technical findings highlighted in this study include the successful demonstration of novel features with mechanism model of carbon-capping in 0-D nanoparticles, horizontal growth formation in 1-D carbon nanotubes and defects enhancement in 2-D graphene films by CVD method. For the electromechanical characterization, it has been demonstrated that the fabricated flexible pressure sensor incorporated with low dimensional carbon based materials can be operated effectively at applied pressure below 10 kPa with high sensitivity, high linearity and high gauge factor in a response to small changes in pressure. The sensitivity of the fabricated sensors with 0-D carbon-capped nanoparticles, 1-D carbon nanotubes and 2-D graphene ultra-thin films in this research was determined to be 0.0148, 0.0109 and 0.0045 kPa-1 with gauge factor of 186, 136 and 32, respectively, in which outperformed the previous findings reported from the literatures. The results also demonstrated that the pressure sensor incorporated with 0-D configuration is more sensitive in a response to applied pressure than 1-D or 2-D configuration, suggesting a significant piezoresistive effect in the reduced dimension. This outstanding result proved that the low dimensional carbon based materials utilized in this present study provide the initial platform for further potential research to achieve the target of ultra-sensitive piezoresistive pressure sensor.